Adapted materials for teaching english to blind and visually impaired students. - Ladino Guzman, Danny Andrey; Vesga Barbosa, Yury Carolina (Corporación Universitaria Minuto de Dios, 2016)
During the training process as future English teachers, it was possible to observe that there are many challenges teachers have to face in the different classrooms they are assigned to teach their classes. One of them was that in the English classes at Uniminuto, where students with diverse abilities and regular ones attend to this course in a same classroom, it was hard for students with visual difficulties to do the activities proposed for the classes. It was because the book was an essential aspect in the classes and, as they have a visual limitation, they could not follow the class in the same way as their sighted peers and, therefore, they were not able to do the activities in the same way. This research project was carried out with the aim of examining the contribution that using adapted materials made to teaching English to blind and visually impaired students. In order to know that, there were created some activities according to the topics that had to be taught in the course and there were designed materials for all students that helped them develop the activities proposed for the classes.
Keywords: English Teachers; Diverse Abilities; Visual Difficulties; Ingles-Enseñanza; Ingles-Uso; Ingles-Gramatical; Ingles-Vocabulario-Enseñanza